Analisis Break Even Point Sebagai Alat Profit Planning Pada Hotel Wijaya Sukabumi - Moch Yusuf Guntara Maulidin; Andri Indrawan; Ade Sudarma (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This research is based on the importance of the management of a company and to know the implement of break event point analysis and the margin of safety in which to study and explore the relationship between costs, profits, and volume of activities. This study aims to determine the break event point approach and the margin of safety as a basis in profit planning. The variables used in this study are Break Event Point and Margin of Safety. The population and sample used are social conditions consisting of three components; places, actors, and activities, with a sampling technique using purposive sampling. Resource persons in the study are the owners, managers, and accountants. This research uses a qualitative method with a descriptive approach. Based on the results of research that Hotel Wijaya in 2018 and 2019 has reached the level of break even point. Margin of safety for 2016 was 41%, in 2017 it was 21%, in 2018 it was 39% and in 2019 it was 35%, while in 2020 Hotel Wijaya planned profit with a percentage of 10% with a total of 104,764,000. Thus, to obtain the profit the Wijaya Hotel must be able to rent out rooms with sales of Rp 355,832,589 with as many as 4,211 units sold. So it can be concluded that the growth of assets and leverage only affects 1.4% of the dividend policy and the rest is influenced by other factors not examined in this study. Keywords: Break Even Point, Profit Planning